Familial neurohypophyseal diabetes insipidus in 13 kindreds and 2 novel mutations in the vasopressin gene. Issue 3 (September 2019) - Patti, Giuseppa; Scianguetta, Saverio; Roberti, Domenico; Di Mascio, Alberto; Balsamo, Antonio; Brugnara, Milena; Cappa, Marco; Casale, Maddalena; Cavarzere, Paolo; Cipriani, Sarah; Corbetta, Sabrina; Gaudino, Rossella; et al.
Abstract : Background: Autosomal dominant neurohypophyseal diabetes insipidus (adNDI) is caused by arginine vasopressin (AVP) deficiency resulting from mutations in the AVP-NPII gene encoding the AVP preprohormone. Aim: To describe the clinical and molecular features of Italian unrelated families with central diabetes insipidus. Patients and methods: We analyzed AVP-NPII gene in 13 families in whom diabetes insipidus appeared to be segregating. Results: Twenty-two patients were found to carry a pathogenic AVP-NPII gene mutation. Two novel c.173 G>C (p.Cys58Ser) and c.215 C>A (p.Ala72Glu) missense mutations and additional eight different mutations previously described were identified; nine were missense and one non-sense mutation. Most mutations (eight out of ten) occurred in the region encoding for the NPII moiety; two mutations were detected in exon 1. No mutations were found in exon 3. Median age of onset was 32.5 months with a variability within the same mutation (3 to 360 months). No clear genotype–phenotype correlation has been observed, except for the c.55 G>A (p.Ala19Thr) mutation, which led to a later onset of disease (median age 120 months). Brain magnetic resonance imaging (MRI) revealed the absence of posterior pituitary hyperintensity in 8 out of 15 subjects, hypointense signal in 4 and normal signal in 2. Follow-up MRI showed the disappearance of the posterior pituitary hyperintensity after 6 years in one case. Conclusion: adNDI is a progressive disease with a variable age of onset. Molecular diagnosis and counseling should be provided to avoid unnecessary investigations and to ensure an early and adequate treatment.